The Role of Medicinal Plants in Treating Intestinal Parasites - Daham , Shahad Saad; Mahmoud, Olfat Raouf; Yonis, Lubna Arkan (American Journal of Biology and Natural Sciences, 2026)
Intestinal parasites are a widespread health problem globally, especially in developing countries, as the rate of infection is closely related to health, social, and environmental conditions, in addition to soil, water, and food contamination with the infectious stages of parasites. Despite the availability of many antiparasitic drugs, their frequent and indiscriminate use has led to the emergence of undesirable side effects, as well as the development of drug resistance in some parasites, which has limited their therapeutic effectiveness. In this context, medicinal plants have gained increasing attention in recent years because they contain effective bioactive compounds that possess antiparasitic properties, as well as being relatively safe natural sources compared to manufactured drugs. This review article aims to examine the therapeutic role of medicinal plants in combating intestinal parasites, highlighting the mechanisms of action of the extracted active compounds and their proven bioavailability in laboratory, animal, and some clinical studies. The results from previous studies indicate that many medicinal plants possess inhibitory activity against the growth and reproduction of intestinal parasites, as well as the ability to enhance the immune response and reduce the severity of infection. This review concludes that medicinal plants represent a promising therapeutic option that could contribute to the development of effective and safe alternatives or complementary therapies for controlling intestinal parasites, while emphasizing the need for deeper future studies to assess safety and clinical efficacy.